Levinas, Simmel, and the Ethical Significance of Money - Christopher Buckman (Religions, 2018)
An examination of Emmanuel Levinas’ writings on money reveals his distance from—and indebtedness to—a philosophical predecessor, Georg Simmel. Levinas and Simmel share a phenomenological approach to analyses of the proximity of the stranger, the importance of the face, and the interruption of the dyadic relationship by the third. Money is closely linked to the conception of totality because money is the medium that compares heterogeneous values. Levinas goes beyond Simmel in positing an ethical relation to money permitting transcendence.